Class I and class II major histocompatibility complex antigens on hepatocytes: importance of the method of detection and expression in histologically normal and diseased livers. - Senaldi, G (1991)
Methodological differences in major histocompatibility complex (MHC) antigen detection were investigated on isolated, viable hepatocytes and cryostat hepatic sections from 27 children with liver disorders, six of whom had normal histology. Class I antigens were constantly found on sections using a three step immunoperoxidase technique after acetone/chloroform fixation, other techniques being less sensitive, or on isolated hepatocytes by indirect immunofluorescence alone. With mechanical isolation the percentage of positivity ranged from 85 to 100%, while with collagenase isolation it ranged from 22 to 49% on immediate testing, and from 53 to 80% after 24 hour incubation. Class II antigens were only detected in one patient with autoimmune chronic active hepatitis and two with primary sclerosing cholangitis. Flow cytofluorimetric analysis in 11 cases confirmed class II or class I positivity, or both, on isolated hepatocytes, allowing MHC antigen expression on hepatocytes to be measured. Class I and II antigen detection on hepatocytes is influenced by the technique used. Although class I antigens are invariably expressed on hepatocytes, class II antigens are only found on hepatocytes from patients with immune mediated liver disorders.